2014
DOI: 10.1155/2014/591489
|View full text |Cite
|
Sign up to set email alerts
|

The Many Faces of Human Leukocyte Antigen-G: Relevance to the Fate of Pregnancy

Abstract: Pregnancy is an immunological paradox, where fetal antigens encoded by polymorphic genes inherited from the father do not provoke a maternal immune response. The fetus is not rejected as it would be theorized according to principles of tissue transplantation. A major contribution to fetal tolerance is the human leukocyte antigen (HLA)-G, a nonclassical HLA protein displaying limited polymorphism, restricted tissue distribution, and a unique alternative splice pattern. HLA-G is primarily expressed in placenta a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 98 publications
3
25
0
1
Order By: Relevance
“…Moreover, proteolytic cleavage of cell surface HLA-G1 by metalloproteinases (MMPs) such as MMP-2 results in another soluble isoform called shedding HLA-G1 ( 17 ). Different HLA-G isoforms are distinguished by the number of extracellular immunoglobulin-like domains and whether intronic sequence encoded residues are included or not; however, all seven reported HLA-G isoforms have the extracellular α1 domain ( 18 ). The conformation of HLA-G1 and -G5 is similar to that of the classical HLA class I antigens, which contain three extracellular domains including α1, α2, and α3 non-covalently bound to β 2 -macroglobulin (β 2 m).…”
Section: Diversity Of the Hla-g Isoformsmentioning
confidence: 99%
“…Moreover, proteolytic cleavage of cell surface HLA-G1 by metalloproteinases (MMPs) such as MMP-2 results in another soluble isoform called shedding HLA-G1 ( 17 ). Different HLA-G isoforms are distinguished by the number of extracellular immunoglobulin-like domains and whether intronic sequence encoded residues are included or not; however, all seven reported HLA-G isoforms have the extracellular α1 domain ( 18 ). The conformation of HLA-G1 and -G5 is similar to that of the classical HLA class I antigens, which contain three extracellular domains including α1, α2, and α3 non-covalently bound to β 2 -macroglobulin (β 2 m).…”
Section: Diversity Of the Hla-g Isoformsmentioning
confidence: 99%
“…It means that HLA-G expression is not strictly associated with protection of embryo/fetus against attack of maternal cells, but it is engaged with tissue remodeling. Expressed or secreted HLA-G molecules by extravillous trophoblast cells (EVT) regulate their decidual and endovascular invasion (10)(11)(12). Namely, EVT cells progressively replace endothelial cells on the walls of uterine spiral arteries, increasing their diameter that ensures proper blood flow to the intervillous space for fetal nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…If this assumption holds true, different properties of sHLA-G and mHLA-G could possibly help clarify discrepancies in HLA-G association studies related to pregnancy complications like preeclampsia. 50 Because novel non-conventional regulatory T cells, which are distinguished by a lower surface expression of CD4 and CD8, were identified in a transplantation study by Naji et al, 51 we sought to investigate whether T cells in placental blood had a decreased surface expression of these markers. Indeed, we found that this was evident for T cells isolated from 'uterine blood'.…”
Section: Discussionmentioning
confidence: 99%